Supervisors' perceptions of organizational policies are associated with their likelihood to accommodate back-injured workers. Issue 4 (13th February 2017) - McGuire, Connor; Kristman, Vicki L.; Shaw, William S.; Loisel, Patrick; Reguly, Paula; Williams-Whitt, Kelly; Soklaridis, Sophie
Abstract: Background Low back pain (LBP) is a major concern among North American workplaces and little is known regarding a supervisor's decision to support job accommodation for workers with LBP. The extent to which supervisors are included in a company's effort to institute disability management policies and practices and workplace safety climate are two factors that may influence a supervisor's decision to accommodate workers with LBP.Objective Determine the association between supervisors' perceptions of disability management policies, corporate safety culture and their likelihood of supporting job accommodations for workers with LBP.Methods We conducted a cross-sectional study of supervisors ( N =796) recruited from a non-random, convenience sample of 19 Canadian and US employers. The outcome was supervisors' likeliness to support job accommodation and the exposure was global work safety culture and disability management policies and practices. A multivariable generalized linear modelling strategy was used and final models for each exposure were obtained after assessing potential effect modifiers and confounders.Results In the study, 796 eligible supervisors from 19 employers participated. Disability management policies and practices were positively associated with supervisors' likeliness to accommodate ( β =0.19; 95% CI: 0.13; 0.24) while no significant association was found between corporate safety culture ( β = −0.084; 95% CI: −0.19; 0.027) and supervisors' likeliness to accommodate.Conclusions Employers should ensure that proactive disability management policies and practices are clearly communicated to supervisors in order to improve job modification and return to work efforts. Implications for Rehabilitation: Low back pain (LBP) is a major workplace concern and little is known regarding what factors are associated with a supervisor's likelihood to support job accommodation for workers with LBP. The objective of this article was to determine the association between supervisors' perceptions of disability management policies and practices, corporate safety culture and their likelihood of support job accommodations for workers with LBP. Results suggest that disability management policies and practices are positively associated with supervisors' likelihood to accommodate while corporate safety culture is not. These results are important for employers as it suggests that employers should ensure that their disability management policies and practices are clearly communicated to supervisors in order to improve job accommodation and return to work efforts.